MOBILE APP DEVELOPMENT FOR THE CONTROL OF PEOPLE INFECTED BY COVID-19 - Núñez Miranda, Carlos (2021)
This article refers to the development of a mobile application intended for prevention, alert and care infections in times of pandemic by COVID-19. The generalization of work and online education from home has caused the immersion of companies, both recognized worldwide and unknown, in the creation of applications to stay connected and linked to carry on production. In addition to that, the current market is based on the download of free and paid applications for Android and IOS that spread COVID-19 information. The application focuses on the knowledge and dissemination of information according to the symptoms that occur in people. It especially focuses on the information provided to different work groups to determine the number of infected people, as well as existing suspicious individuals, to subsequently, make the corresponding notifications in order to take actions for prevention or for the application of security measures (epidemiological fences), to avoid further infections